2021
DOI: 10.1371/journal.pone.0255653
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the relationship between air pollution and various types of crime

Abstract: Air pollution has a severe impact on human physical and mental health. When the air quality is poor enough to cause respiratory irritation, people tend to stay home and avoid any outdoor activities. In addition, air pollution may cause mental health problems (depression and anxiety) which were associated with high crime risk. Therefore, in this study, it is hypothesized that increasing air pollution level is associated with higher indoor crime rates, but negatively associated with outdoor crime rates because i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…At the same time, air pollution can also have a serious impact on human behavior. Lin et al (2022) found that air pollution makes people get jobs nearby, and it also makes people move away from heavily polluted residential areas (Yang et al, 2022), and even increases people's crime rate (Kuo and Putra 2021). However, Chang et al (2016) showed in a study of a pear-packing plant that PM 2.5 with high penetration capacity in outdoor air significantly reduced the productivity of indoor workers, while pollutants with low penetration capacity (e.g., ozone) had almost no significant effect.…”
Section: Literature Review and Mechanism Analysismentioning
confidence: 99%
“…At the same time, air pollution can also have a serious impact on human behavior. Lin et al (2022) found that air pollution makes people get jobs nearby, and it also makes people move away from heavily polluted residential areas (Yang et al, 2022), and even increases people's crime rate (Kuo and Putra 2021). However, Chang et al (2016) showed in a study of a pear-packing plant that PM 2.5 with high penetration capacity in outdoor air significantly reduced the productivity of indoor workers, while pollutants with low penetration capacity (e.g., ozone) had almost no significant effect.…”
Section: Literature Review and Mechanism Analysismentioning
confidence: 99%
“…Air pollution, specifically exposure to PM2.5, has been associated with violent crime (Herrnstadt et al, 2018). Poor air quality has been associated with higher rates of domestic assault (more relevant to an impulsive and reactive act of aggression), to a lesser extent property damage (an act at least somewhat related to impulsivity and cognitive / emotional state), and no relation to cybertheft (P.-F. Kuo & Putra, 2021). These findings suggest that air pollution may be specifically increasing crimes that are affected by individuals' cognitive and emotional states, relating to acts more associated with reactive aggression and impulsivity than "cold", pro-active criminal activity.…”
Section: Impulsivity Aggression and Other Environmental Factorsmentioning
confidence: 99%
“…With large-scale industrialization and extensive use of fossil fuels, air pollution strongly affects the quality of human life. Recent theoretical developments have revealed that heavy air pollution from hazy weather not only poses a great threat to physical health but also exacerbates mental health problems and even leads to depression (Gladka et al, 2022), suicide (Sun et al, 2020), and violent crime (Kuo & Putra, 2021).…”
Section: Introduction 1project Backgroundmentioning
confidence: 99%